1999
DOI: 10.1016/s0378-1097(99)00295-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fluorescent amplified fragment length polymorphism (FAFLP) methodology for the genotypic discrimination of Aeromonas taxa

Abstract: A fluorescent amplified fragment length polymorphism (FAFLP) fingerprinting assay is evaluated for its ability to differentiate DNA hybridization groups in the genus Aeromonas. After empirical determination of optimal assay conditions using a limited set of strains, 98 well-characterized type and reference strains encompassing all known Aeromonas taxa were subjected to FAFLP fingerprinting using the standardized protocol. The present study clearly indicates that the use of fluorescent dye-labeled primers does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Strains of type BD-2 displayed high haemolytic and cytotoxic activities and were identified by fatty acid analysis as members of Aeromonas hydrophila DNA hybridization group (HG) 1. Comparison with a genotypic database generated from amplified fragment length polymorphism (AFLP) fingerprinting patterns also allocated the BD-2 isolates to Aeromonas (Huys & Swings, 1999). Clustering was obtained following numerical analysis of digitized FAFLP band patterns using Pearson's product-moment correlation coefficient (expressed as percentages) and the unweighted paired group method using arithmetic means.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Strains of type BD-2 displayed high haemolytic and cytotoxic activities and were identified by fatty acid analysis as members of Aeromonas hydrophila DNA hybridization group (HG) 1. Comparison with a genotypic database generated from amplified fragment length polymorphism (AFLP) fingerprinting patterns also allocated the BD-2 isolates to Aeromonas (Huys & Swings, 1999). Clustering was obtained following numerical analysis of digitized FAFLP band patterns using Pearson's product-moment correlation coefficient (expressed as percentages) and the unweighted paired group method using arithmetic means.…”
mentioning
confidence: 99%
“…All strains were cultured aerobically on Trypticase soy agar (TSA), containing 3 % (w\v) Trypticase soy broth (BBL) and 1n5% (w\v) bacteriological agar no. 1 (Oxoid), at 28 mC for 24 h. All BD-2 isolates were subjected to FAFLP fingerprinting and the resulting FAFLP profiles were compared with the laboratory-based AEROLIB database (Huys & Swings, 1999). Microscale DNA extraction, AFLP template preparation, selective PCR amplification, electrophoresis on an automated DNA sequencer and data processing were performed as described previously (Huys & Swings, 1999).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterium has remained within the family Vibrionaceae until molecular studies carried out by Martinez-Murcia et al [8] indicated that P. shigelloides is phylogenetically related to the genus Proteus. Furthermore, Huys and Sings [9] in an evaluation of the amplified fragment length polymorphism technique for genotyping Aeromonas spp. found that P. shigelloides clearly falls out of the major Aeromonas cluster.…”
Section: Introductionmentioning
confidence: 99%